SAT0307 Jaccoud Arthropathy in Systemic Lupus Erythematosus: Association between Anti-Citrullinated Protein Antibodies and Erosive Damage. (15th July 2016) - Massaro, L.; Ceccarelli, F.; Pendolino, M.; Perricone, C.; Cipriano, E.; Truglia, S.; Miranda, F.; Spinelli, F.R.; Alessandri, C.; Valesini, G.; Conti, F.
Abstract : Background: Jaccoud arthropathy (JA) is a deforming, non-erosive arthritis, occurringin 2–35% of Systemic Lupus Erythematosus (SLE) patients. The deformities could be easily misdiagnosed as those identified in rheumatoid arthritis (RA), even though, unlike in RA, they are reducible. To date no specific markers for JA are available. The evaluation of Rheumatoid Factor (RF) and anti-citrullinated protein antibodies (ACPA) in JA patients demonstrated a higher frequency of RF in comparison with SLE patient without JA. No differences in ACPA positivity were found. Imaging techniques could be helpful in the assessment of JA: the traditional radiographic definition of non-erosive arthropathy has been modified in the last years thanks to the use of new imaging techniques such as ultrasonography (US). So far, small JA populations have been evaluated by US, identifying the presence of mild articular and peri-articular involvement. Objectives: The aim of the present study was to evaluate the prevalence of JA in a wide monocentric cohort of SLE patients and to describe clinical, serological and ultrasonographic features in this subset of patients. Methods: Consecutive SLE patients (ACR criteria 1997) were evaluated. JA index was applied for patients with reducible deformities. Patients with JA index ≥5 underwent physical examination, blood draws and US assessment. ACPA and RF was detected by using the commercial ELISA kit. We compared JA patients with a subgroup of 62 SLE patients, age and sex matched, with joint involvement without JA. A single rheumatologist performed the US assessment of bilateral wrist and hands. All abnormalities were evaluated according to the OMERACT definitions. Results: Four hundred eighty SLE patients were evaluated: 17 (3.5%) showed a JA index ≥5 (M:F 1:16; mean age±SD 50.7±11.1 years; mean disease duration±SD 247.8±116.2 months). The most frequent deformity was ulnar drift of MCP joints (88.2%).RF resulted significantly more frequent in JA patients compared with ACPA (41.2% versus 23.5%, P=0.009). We compared the frequency of RF and ACPA in JA patients with a subgroup of 62 SLE patients, age and sex matched, with joint involvement without JA. JA patients showed a significantly higher frequency of RF than SLE patients without JA (41.2% vs 17.7%, respectively; P=0.0006). Conversely, no significant difference in ACPA frequency was found between these two groups of patients. No differences were found in the titre of ACPA and RF. Bone erosions, in at least one joint, have been found in 10 JA patients (58.8%) and the most frequent joints involved were I and II MCP (17.6% of the patients for both joints). Subgrouping JA patients according with ACPA status, ACPA+ patients showed significantly more frequent erosive damage compared with ACPA- (75% versus 53.8%, P=0.002). Conclusions: The present study identified an association between ACPA positivity and erosive damage in JA patients. These results suggest the possibility to use ACPA as a marker of severity in this subgroup of SLE patients, driving therapeutical approach in order to prevent chronic damage accrual. Disclosure of Interest: None declared